PERLINDUNGAN MEREK DAGANG PADA PLATFORM E-COMMERCE DI INDONESIA DITINJAU DARI PERSPEKTIF HAM - Kennedy, Alexander; Wartoyo, Franciscus Xaverius (Fakultas Hukum Universitas Islam Indonesia, 2024)
The growth of e-commerce transactions in Indonesia reached 533 trillion Rupiah in 2023, reflecting a significant transformation in the national business landscape. This increase opens new opportunities for companies to expand their markets but also presents challenges related to business competition and intellectual property rights protection. Trademarks, as valuable assets representing the reputation and quality of products, require effective protection to build consumer trust and maintain brand integrity. This protection becomes increasingly crucial in the digital era due to the rising cases of trademark infringements, including unauthorized use and counterfeiting. This study highlights the importance of adaptive legislation and the role of technology in detecting counterfeit products in e-commerce. By employing normative juridical methods, this research analyzes the effectiveness of regulations and practices in trademark protection in Indonesia, comparing them with best practices in other countries. The study also evaluates the impact of trademark protection on human rights, emphasizing that the right to a trademark is part of intellectual property rights that protect the economic and social interests of trademark owners. E-commerce platforms play a crucial role in protecting trademarks by implementing internal policies, reporting mechanisms, and cooperation with relevant authorities. Despite progress, challenges remain, particularly in monitoring the large volume of products and addressing increasingly sophisticated infringement methods. Effective trademark protection not only enhances consumer trust but also fosters innovation and digital economic growth. This research provides recommendations to improve collaboration between the government, e-commerce platforms, and trademark owners in protecting intellectual property rights in Indonesia.